Changes In Soil Algocenoses In Steep Regions (Eurasian Journal of Research, Development and Innovation, 2024)
In this article, the number and diversity of species of soil algocenoses distributed in the steep regions of the northern, southern, eastern and western parts of the Fergana Valley were taxonomically analyzed. According to it, Cyanophyta, Xanthophyta, Bacillariophyta, Chlorophyta, Euglenophyta and Cryptophyta divisions have 73-79 species in the plain regions, 62-68 species in the hills, 54-59 species in the foothills and 42-45 species in the mountains. considered.